ХАЛЫҚ ДӨРЕТИЎШИЛИГИНДЕГИ АҚЫЛ-ТӘРБИЯСЫ АРҚАЛЫ ЖАСЛАРДА МИЛЛИЙ ИДЕЯНЫ ҚӘЛИПЛЕСТИРИӮ МӘСЕЛЕЛЕРИ - Тилегенов, А.Т. (FAN va JAMIYAT, 2024)
This article examines the issues of forming a national idea among young people through intellectual education through folk art. The importance of mental education in the spiritual development of a person is also discussed.